Current issues in therapy of vaginal infections during gestation - Yu E Dobrokhotova; L A Ozolinia; K R Bondarenko; I A Lapina; A S Dvornikov (IP Berlin A.V., 2016)
Infections of the reproductive tract caused by various representatives of the vaginal microbiota have been associated with increased risk of pregnancy complications. This review presents the current data from the literature on the role of bacterial vaginosis and vulvovaginal candidiasis in the development of obstetric complications. Standard therapy of vaginal infections has a number of restrictions: in some cases it can cause adverse events and side effects, sometimes it can be ineffective if it is necessary to achieve complex effects on pathogens in mixed infections. As an alternative drug for the treatment of bacterial vaginosis and vulvovaginal candidiasis intravaginal use of the drug with an antiseptic effect (dequalinium chloride 10 mg, which confirmed its safety and efficacy in clinical studies conducted with the participation of more than 3000 women) is proposed.